Lexical Means of Nomination a Person in Russian Ditties - Kazachuk, I.G. (2020)
The article is devoted to the actual problem of the variety of means of nomination for men and women in the structure of the lively folk genre of the ditty. The focus is on the nominations of a person as a significant set of ideas about a language personality within Russian national culture. Units of the nomination of the masculine and feminine are the most frequent ones in the structure of the ditty genre, compared to other folklore genres and literary language. Gender reflects a person's mental perception of man and woman, male and female. The work focuses on the nominates representing the man in terms of psychology, ethics, morals, social ties.